Cyber ​​Crime Crimes in Indonesian Law and Efforts to Prevent and Handle Cyber ​​Crime Cases - Syalendro, Oky; Lubis, Arief Fahmi; Putra, R Yusak Andri Ende (CV. Rayyan Dwi Bharata, 2025)
Cybercrime refers to crimes conducted through computer networks and the internet, encompassing various illegal activities such as data theft, online fraud, hacking, and malware distribution. In Indonesia, regulations concerning cybercrime are primarily governed by Law Number 11 of 2008 on Electronic Information and Transactions (EIT Law), which was later amended by Law Number 19 of 2016. The handling of cybercrime in Indonesia has evolved alongside rapid digitalization, particularly in the financial, telecommunications, and social media sectors.This study aims to analyze the application of cybercrime laws in Indonesia and the challenges faced in law enforcement. Additionally, it examines the preventive efforts made by various stakeholders, including the government, private sector, and the public, through the strengthening of security infrastructure, digital literacy campaigns, and international collaboration in tackling cybercrime.The research methodology used in this study is normative juridical with a legislative and case study approach. The author examines various regulations, including the EIT Law and the Personal Data Protection Law, as well as notable cybercrime cases in Indonesia, such as ransomware attacks on hospitals and data theft in the banking sector.The study concludes that while Indonesia has a strong legal framework for addressing cybercrime, challenges remain in the ability of law enforcement to apply digital forensic technology, low public digital literacy, and suboptimal international cooperation. Therefore, strengthening law enforcement capacity, developing data protection policies, and increasing public awareness are necessary to address the growing cybercrime threat.